(untitled) (Dhaka University Journal of Science, 2017)
Steady-state laminar combined convection flow of an electrically conducting, non-Newtonian fluid past a sphere is studied numerically. The effects of the power-law index, the mixed convection parameter, the magnetic field parameter and the heat generation or absorption parameter on the skin friction and the heat transfer are illustrated. The skin friction for dilatant fluids is smaller than that for pseudoplastics. Near the stagnation point, the Nusselt number reduces rapidly for pseudoplastics and reaches sharply a maximum value for dilatant fluids. Both the skin friction and the Nusselt number decrease owing to an increase of the magnetic field parameter. Moreover the heat generation produces higher skin friction and lower Nusselt number. Dhaka Univ. J. Sci. 65(1): 21-25, 2017 (January)